(untitled) (Journal of Pharma Insights and Research, 2024)
Herbal remedies, used for millennia, require rigorous safety, efficacy, and quality evaluations due to their widespread use. Assessing the toxicity of herbal remedies involves multifaceted approaches including in vitro and in vivo methodologies, clinical trials, and regulatory frameworks. Acute, sub-acute, and chronic toxicity testing paradigms are crucial for establishing dose-response relationships and identifying potential risks. The complexity of toxicity assessment in herbal products stems from their multi-component nature and potential interactions. Advanced analytical techniques such as high-performance liquid chromatography (HPLC), mass spectrometry (MS), and nuclear magnetic resonance (NMR) spectroscopy play a vital role in identifying and quantifying potentially toxic compounds. Pharmacovigilance is essential for monitoring adverse reactions and ensuring long-term safety. The regulatory landscape surrounding herbal medicines varies globally, highlighting the need for harmonized standards. Emerging technologies like -omics approaches and in silico modelling promise to revolutionize toxicity assessments. Current knowledge synthesis reveals critical gaps in herbal remedy toxicity assessment methods. These tools and methodologies are crucial for safeguarding public health and integrating herbal medicine into modern healthcare systems, emphasizing the importance of continued research and development in this field